Legal Protection of Women Victims of Sexual Harassment in Indonesia - Tri Astuti Handayani; Teguh Prasetyo; Diding Rahmat (UNIFIKASI : Jurnal Ilmu Hukum, 2019)
The rise of sexual and non-verbal sexual harassment against women by men makes women not have bargaining in criminal law as a victim, this has implications for the psychology of women feeling humiliated, lacking confidence, trauma and fear, due to the above women who are victims of sexual harassment who are unable to carry out their work or even have mental illness, stress or some who commit suicide. The purpose of this study was to determine the legal arrangements for the protection of women due to acts of sexual harassment by men today and how the legal efforts of victims of sexual harassment against women. The methodology used in this study is normative legal research with primary, secondary and tertiary materials such as laws, journals and books. The researcher concludes:  First; There is a need for regulations governing the protection of women, especially regarding acts of sexual harassment. Second; Preventive and repressive efforts are needed to prevent acts of sexual harassment against women in order to protect women so that women are able to rise up, advance, prosperous, happy, independent and contribute to the Family, Nation and State. Preventive efforts can be carried out through socialization, workshops and training on legal awareness of women's protection while repressive efforts include taking action by the police.Keywords: Women, Sexual Harassment, Legal Protection Perlindungan Hukum terhadap Perempuan Korban Pelecehan Seksual di Indonesia Abstrak : Maraknya tindakan pelecehan seksual baik verbal maupun non verbal terhadap perempuan yang dilakukan oleh laki laki menjadikan perempuan tidak memliki bergaining dalam hukum pidana sebagai korban, hal demikian berimplikasi pada pisikologi perempuan merasa direndahkan, kurang percaya diri, trauma dan takut, akibat hal di atas perempuan yang menjadi korban pelecehan seksual yang tidak bisa menjalankan pekerjaanya atau pun ada juga sakit jiwa, stress atau ada juga yang bunuh diri. Tujuan penelitian ini untuk mengetahui pengaturan hukum perlindungan perempuan akibat tindakan pelecehan seksual oleh laki-laki saat ini serta bagaimana upaya hukum korban pelecehan seksual terhadap perempuan. Metodelogi yang dipakai dalam penelitian ini adalah penelitian hukum yuridis normatif dengan bahan primer, sekunder dan tersier seperti peraturan perundang undangan, jurnal dan buku. Hasil penelitian  Pertama; Perlu adanya peraturan yang mengatur mengenai perlindungan perempuan khusunya mengenai tindakan pelecehan seksual. Kedua; Perlu adanya upaya preventif dan represif dalam mencegah tindakan pelecehan seksual terhadap perempuan dalam rangka melindungi para perempuan agar perempuan mampu bangkit, maju, sejahtera, bahagia, mandiri dan berkontribusi bagi Keluarga, Bangsa dan Negara . Upaya preventif dapat dilakukan dengan sosialisasi, workshop dan pelatihan-pelatihan kesadaran hukum perlidungan perempuan sedangkan upaya refresif berupa penindakan oleh aparat kepolisian.Kata Kunci :  Perempuan, Pelecehan Sekual, Perlindungan Hukum